2019
DOI: 10.1088/1367-2630/ab0457
|View full text |Cite
|
Sign up to set email alerts
|

Topological node line semimetal state in two-dimensional tetragonal allotrope of Ge and Sn

Abstract: Realizing semimetal states in two-dimensional (2D) materials are of great importance for their future application in novel quantum devices at the nanoscale. Using first-principles calculations based on density functional theory, we propose a new 2D tetragonal allotrope of Ge and Sn, 2D T-Ge and T-Sn, which consists of repeated square and octagon rings. The calculated cohesive energy, ab initio molecular dynamic simulations and phonon dispersions indicate that 2D T-Ge and T-Sn are stable at room temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 60 publications
(69 reference statements)
1
25
0
Order By: Relevance
“…Being the 2D limit of haeckelite compounds with P4 2 /mnm space group, they exhibit a range of phases. For example, T-structures of single layers of pure Si and C behave as Dirac semimetal, [30,31] Ge and Sn as topological nodal line semimetals, [32,33] and P, As, Sb, and Bi as trivial band insulators. [34][35][36] On the other hand, T-structures of single or bilayers of III-V (AlN, GaN) [37,38] or VA-VA (SbBi, AsBi, PBi, AsSb, PAs) [39] element compounds are mostly semiconducting.…”
Section: Introductionmentioning
confidence: 99%
“…Being the 2D limit of haeckelite compounds with P4 2 /mnm space group, they exhibit a range of phases. For example, T-structures of single layers of pure Si and C behave as Dirac semimetal, [30,31] Ge and Sn as topological nodal line semimetals, [32,33] and P, As, Sb, and Bi as trivial band insulators. [34][35][36] On the other hand, T-structures of single or bilayers of III-V (AlN, GaN) [37,38] or VA-VA (SbBi, AsBi, PBi, AsSb, PAs) [39] element compounds are mostly semiconducting.…”
Section: Introductionmentioning
confidence: 99%
“…19 Not only carbon, Si and Ge also form buckled tetragonal allotropes named tetragonal silicene and germanene. 20,21 These tetragonal forms also exhibit node-line semimetal with double Dirac cones. 22 On the other hand, research related to group-V elements got boosted after the synthesis of phosphorus thin films.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In 2012, Wang et al established the stability and electronic characteristics of the armchair and zigzag T-graphene nanoribbons . Besides, extensive research has revealed applications of T-graphene in various intriguing fields, such as in gas sensors, , hydrogen storage, , current rectification devices, and optoelectronic devices. Similar to graphene, the hexagonal forms of Si and Ge are the next two stable candidates from the same group. One of the major advantages of working with silicene and germanene is that considering the spin–orbit coupling effects, the zero-band-gap feature can be avoided. , Recently, the tetragonal counterparts of Si and Ge, i.e., T-Si and T-Ge, have been predicted to be stable on satisfying various stability criteria. Contrary to planar T-graphene, T-Si and T-Ge possess semimetallic band structures with double Dirac cones. , To generate and tune the band gap in these tetragonal systems, several approaches have been taken. , Hence, relative to T-graphene, T-Si and T-Ge are expected to be better candidates for nanodevice applications.…”
Section: Introductionmentioning
confidence: 99%